When rituals go wrong : mistakes, failure and the dynamics of ritual - Hüsken, Ute. (Numen Book Series, 2007)
The present volume is entirely dedicated to the investigation of the implications and effects of breaking ritual rules, of failed performances and of the extinction of ritual systems. While rituals are often seen as infallible mechanisms which 'work' irrespective of the individual motivations of the performers, it is clearly visible here that rituals can fail, and that improper performances do in fact matter. These essays break new ground in their respective fields and the comparative analysis of rituals that go wrong introduces new perspectives to ritual studies. As the first book-length study on ritual mistakes and failure, this volume begins to fill a significant gap in the existing literature. Contributors include: Claus Ambos, Christiane Brosius, Johanna Buss, Burckhard Dücker, Christoph Emmrich, Brigitta Hauser-Schäublin, Maren Hoffmeister, Ute Hüsken, Brigitte Merz, Axel Michaels, Karin Polit, Michael Rudolph, Edward L. Schieffelin, Jan A.M. Snoek, Eftychia Stavrianopoulou, and Jan Weinhold.